Ecological Treatment and Resource Utilization of Wastewater from a Chicken Transfer Station - Rongwei Xiong; Xiufang Gao; Jinquan Huang; Yilin Mao; Peihua Jiang; Li Jiang (Adsorption Science & Technology)
Research was conducted at a chicken transfer station to assess ecological treatment and resource utilization. The study examined three aspects: wastewater ecological treatment, resource utilization maximization, and process optimization. Process design and operation monitoring were carried out to treat and reuse wastewater from a chicken feeder station over two periods. The first period was operated in 2014, adopting the mode of pretreatment plus a constructed wetland. Results show that the relevant indicators basically meet the regulatory requirements at that time. The second period carried out in 2017 improved upon the results obtained during the first period. On the basis of strengthening the pretreatment and constructed wetland functions, full recycling of tailwater and zero discharge of wastewater was achieved. The aquatic plant water celery used for wetland wastewater purification function also reached the standard of safe vegetable consumption, producing systematic ecological and economic benefits. The second phase of the project has high promotion and application value in the wastewater treatment of the chicken transfer station. This study demonstrates an improved approach to poultry production wastewater treatment by transforming wastewater into an agricultural product while achieving wastewater reuse and environmental pollution control.